1982
DOI: 10.1002/ddr.430020205
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of shock‐suppressed behavior by treatment with (+)‐5‐methyl‐10,11‐dihydro‐5H‐dibenzo[a, d]cyclohepten‐5, 10‐imine (MK‐801), a substance with potent anticonvulsant, central sympathomimetic, and apparent anxiolytic properties

Abstract: MK‐801 was evaluated in rats for “antipunishment” and “anticonflict” activity in two procedures: (1) A conditioned emotional response (CER) test involving the suppression of lever‐pressing by unaviodable shock and (2) a simple conflict test in water‐deprived animals that were shocked for licking water. The effect of MK‐801 in both procedures was qualitatively similar to the benzodiazepines. Lever‐pressing in the CER test was increased by MK‐801 at doses ranging from 50–400 μg/kg administered orally (p.o.) at e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
0

Year Published

1982
1982
1997
1997

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 138 publications
(18 citation statements)
references
References 28 publications
1
17
0
Order By: Relevance
“…The compound is MK-801 {(+)-5- (Fig. 1), a substance previously reported to possess an unusual spectrum of pharmacological activities as a potent anticonvulsant that exhibits both anxiolytic and sympathomimetic properties (9)(10)(11).…”
mentioning
confidence: 99%
“…The compound is MK-801 {(+)-5- (Fig. 1), a substance previously reported to possess an unusual spectrum of pharmacological activities as a potent anticonvulsant that exhibits both anxiolytic and sympathomimetic properties (9)(10)(11).…”
mentioning
confidence: 99%
“…It has been reported that MK-801 shows anticonvulsant action (2), neuroprotective ac tion (3), an antiparkinson property (4), and anticonflict action (5,6). Furthermore, Clineschmidt et al (7) demonstrated that MK 801 increased the ambulatory activity of mice and produced an ipsilateral turning in the rat with unilateral nigrostriatal lesion, indicating that MK-801 possesses agonistic action on cen tral dopaminergic systems through an accelera tion of the dopaminergic transmission.…”
mentioning
confidence: 99%
“…Both of these substances have been reported to exert anxiolytic effects in animal models [Stephens et al, 1986;Clineschmidt et al, 19821, but both compounds are better known for their anticonvulsant and muscle-relaxant properties [Clineschmidt et al, 1982;Meldrum and Chapman, 1986;Turski et al, 19851. In this experiment, both substances exerted strong sedative effects and could not be tested at higher doses on the cue.…”
Section: Discussionmentioning
confidence: 97%